Industrial Revolution Ideas 4.0 for Professional Development - Anizira Anizira; Chevy Herli Sumerli A; Rizki Alfadillah Nasution; Zarkasi Zarkasi; Arief Yanto Rukmana (Pusat Riset dan Inovasi Nasional, 2023)
The company strives to achieve the development of human resources and employee work abilities in the era of the industrial revolution 4.0 in order to achieve appropriate employee work efficiency. The achievement of employee work efficiency is seen based on what kind of employee development takes place. how the company places employees in positions that match what the employee has. By using brainstorming variables using a quantitative approach method with data in the form of primary and secondary data, the sample used was 76 employees. Based on the results of direct and indirect hypothesis testing, there is development of human resources and employee work abilities in the era of the 4th industrial revolution.